An Investigation of Oxidative DNA Damage in Pharmacy Technicians Exposed to Antineoplastic Drugs in Two Chinese Hospitals Using The Urinary 8-OHdG Assay - HUANG, Yu Wen; JIAN, Le; ZHANG, Mei Bian; ZHOU, Quan; YAN, Xiao Feng; HUA, Xu Dong; ZHOU, Ying; HE, Ji Liang (Biomedical and environmental sciences, 2012)
Objective To investigate oxidative DNA damage in pharmacy technicians preparing antineoplastic drugs at the PIVAS （Pharmacy Intravenous Admixture Service） in two Chinese hospitals. Methods Urinary 8-OHdG served as a biomarker. 5-Fluorouracil （5-FU） concentrations in air, masks and gloves were determined. The spill exposure of each PIVAS technician to antineoplastic drugs was investigated. Eighty subjects were divided into exposed group t, II, and control group I, II. Results 5-FU concentration ratios for gloves and masks in exposed group I were significantly higher than those in exposed group II （P〈0.05 or P〈0.01）. The average urinary 8-OHdG concentrations in exposed group I, control group I, exposed group II, and control group II were 24.69＋0.93, 20.68＋1.07, 20.57＋0.55, and 12.96_＋0.73 ng/mg Cr, respectively. Urinary 8-OHdG concentration in exposed group I was significantly higher than that in control group I or that in exposed group 11 （P〈0.02）. There was a significant correlation between urinary 8-OHdG concentrations and spill frequencies per technician （P〈0.01）. Conclusion There was detectable oxidative DNA damage in PIVAS technicians exposed to antineoplastic drugs. This oxidative DNA damage may be associated with their spill exposure experience and contamination of their personal protective equipment.